The Narrative of Criminal Behaviour in Indonesian Literature by Female Author: Psychosocial Criminology Perspective - Ahmadi, Anas (International Journal of Criminology and Sociology, 2021)
Criminology studies, currently, are the most discussed subject from interdisciplinary perspectives. Hence, in this research, Indonesian literature written by the female author is studied using a psychosocial criminology perspective. One of the female authors in Indonesia who brings up criminology in her literary work is Dewi Lestari. She is an Indonesian novelist. The research problems are 1) How criminology depicted in Indonesian literature written by the female author is, and 2) Types of criminology depicted in Indonesian literature written by a female author. The method used in this research is qualitative interpretative. The collecting data technique in the literature study. The result shows that criminology in Indonesian literature is depicted explicitly. Whereas, types of criminology in Indonesian literature written by the female author are corruption, sex crimes, and transnational crimes related to endangered animal trade.